Liver esterase polymorphisms in sepat Siam (Trichogaster pectoralis) - Tan, S. K.; Gan, Yik Yuen; Tan, Soon Guan (Universiti Pertanian Malaysia, 1980)
Esterase D and general esterases (which use a- or J3-naphthyl acetate as substrates) were investigated electrophoretically in the paddy field fish, Trichogaster pectoralis. Variants were observed for these enzymes. It is hypothesized that esterase D phenotypes are due to two codominant alleles at an autosomal locus, and that four loci are involved in the control of the general esterases.